Representations of Diversity in L'Oréal Paris Advertisements in Europe and Asia - Azhar, Muhammad Fauzan; Fitriyah, Ulil (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Asia and Europe have different perspectives on beauty standards. In Asia, fair skin is often considered the ideal, while in Europe, there is often a greater appreciation for diverse skin tones and natural physical features. The study analize diversities shown in Europe and Asia L'oréal Paris beauty advertisements. This research aims to analyze and understand various aspects of diversity presented in L'Oréal Paris beauty advertisements in Europe and Asia. In this study, the L'oréal Groupe Youtube channel was chosen to represent the L'Oréal Paris beauty product advertisement in Europe and the L'Oréal Paris Singapore, L'Oréal Paris Malaysia and L'Oréal Paris India were chosen to represent the L'Oréal Paris beauty product advertisement in Asia. The study elaborated on comparative research with the semiotic theory put forward by Roland Barthes in analyzing L'Oréal Paris advertisement which was broadcast on the YouTube channels of both regions. This study considered elements such as ethnicity, gender, age, and the concept of beauty depicted in the advertisements. The present study highlights Both Asian and European L'Oréal Paris advertisements predominantly feature women, albeit with different focuses. In Asia, there is a stronger emphasis on women's empowerment, symbolizing progress and changing roles for women in society. This messaging aligns with cultural contexts in some Asian countries that may still uphold traditional gender ideologies. On the other hand, European advertisements emphasize diversity and inclusivity, celebrating a wide range of backgrounds, appearances, and personalities among models.